LIM kinase-1 selectively promotes glycoprotein 1b-IX-mediated TXA2 synthesis, platelet activation, and thrombosis - Estevez, Brian; Stojanovic, Aleksandra; Delaney, M Keegan; O'Brien, Kelly; Berndt, Michael; Ruan, Changgeng; Du, Xaioping (American Society of Hematology, 2013)
Current antithrombotic drugs have an adverse effect on bleeding, highlighting the need for new molecular targets for developing antithrombotic drugs that minimally affect hemostasis. Here we show that LIMK1−/− mice have defective arterial thrombosis in vivo but do not differ from wild-type mice with respect to bleeding time. LIMK1−/− mice show a selective defect in platelet activation induced through the von Willebrand Factor (VWF) receptor, the glycoprotein Ib-IX-V complex (GPIb-IX), but not by GPIb-IX–independent platelet agonists. In fact, LIMK1−/− platelets show an enhanced reaction to certain GPIb-IX–independent agonists. The defect of LIMK1−/− platelets in GPIb-IX–mediated platelet activation is attributed to a selective inhibition in VWF/GPIb-IX–induced phosphorylation of cytosolic phospholipase A2 (cPLA2) and consequent thromboxane A2 (TXA2) production. Supplementing a TXA2 analog, U46619, corrected the defect of LIMK1−/− platelets in VWF-induced stable platelet adhesion. Although LIMK1−/− platelets also showed reduced actin polymerization after GPIb-IX–mediated platelet aggregation, actin polymerization inhibitors did not reduce TXA2 generation, but rather accelerated platelet aggregation, suggesting that the role of LIMK1 in GPIb-mediated platelet activation is independent of actin polymerization. Thus, LIMK1 plays a novel role in selectively mediating GPIb-IX–dependent TXA2 synthesis and thrombosis and represents a potential target for developing antithrombotic drugs with minimal bleeding side effect.